Mosaic pattern of Borrelia infection in a continuous population of the tick Ixodes ricinus (Acari: Ixodidae) - Zeman, P; Daniel, M (Experimental & applied acarology, 1999)
An array of 12 20 x 20 m quadrats in a mixed forest near Poteply, Central Bohemia, Czech Republic, was investigated for the abundance and spatial distribution of host-questing Ixodes ricinus nymphs and their infection with borreliae. Tick densities were estimated by flagging and their borrelia infection status was determined by direct immunofluorescence. While the tick population appeared to be continuous and homogeneous based on quadrat counts, their infection with borreliae evinced a mosaic pattern. The nymphal infection rates ranged between 1.6 and 10.5% (mean = 6.0%) with significant differences between adjacent quadrats. Home ranging of small rodents (Apodemus flavicollis and Clethrionomys glareolus) inhabiting the forest seems to be responsible for the spatial pattern of borrelial infection.
Keywords: protilátky bakteriální; lymeská nemoc; Animals; fluorescenční protilátková technika přímá; nemoci hlodavců; klíště; Rodent Diseases; infestace klíšťaty; Rodentia; nymfa; Borrelia burgdorferi komplex; Antibodies, Bacterial; Borrelia burgdorferi Group; Nymph; Czech Republic; Lyme Disease; Česká republika; hlodavci; zvířata; Fluorescent Antibody Technique, Direct; Tick Infestations; Ixodes